2017
DOI: 10.3390/toxins9110376
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicle Involvement in Shiga Toxin-Associated Infection

Abstract: Shiga toxin is the main virulence factor of enterohemorrhagic Escherichia coli, a non-invasive pathogen that releases virulence factors in the intestine, causing hemorrhagic colitis and, in severe cases, hemolytic uremic syndrome (HUS). HUS manifests with acute renal failure, hemolytic anemia and thrombocytopenia. Shiga toxin induces endothelial cell damage leading to platelet deposition in thrombi within the microvasculature and the development of thrombotic microangiopathy, mostly affecting the kidney. Red b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 200 publications
(284 reference statements)
0
22
0
Order By: Relevance
“…Indeed, lipid rafts contain caveolin where polymerization provides the platform on which to form early endosomes. The mobilization of microtubular units bring into play both clathrin-dependent [150,152] and clathrin-independent pathways [153,154]. Next, the Stx-Gb3 complex is addressed from early endosomes to the endoplasmic reticulum though retrograde transport, making it possible for Stx Gb3 to escape lysosomal degradation [155].…”
Section: Shiga Toxin Production and Effect: Gb3 Fixation And Traffickingmentioning
confidence: 99%
“…Indeed, lipid rafts contain caveolin where polymerization provides the platform on which to form early endosomes. The mobilization of microtubular units bring into play both clathrin-dependent [150,152] and clathrin-independent pathways [153,154]. Next, the Stx-Gb3 complex is addressed from early endosomes to the endoplasmic reticulum though retrograde transport, making it possible for Stx Gb3 to escape lysosomal degradation [155].…”
Section: Shiga Toxin Production and Effect: Gb3 Fixation And Traffickingmentioning
confidence: 99%
“…Stahl et al found that Stx2 was present within blood cell-derived microvesicles taken up by renal cortical cells during Shiga toxin-associated infection leading to cell death. This was also observed in Stx2 treated mice and confirmed in in vitro studies, which showed that Stx2-containing blood cell-derived microvesicles undergo endocytosis in glomerular endothelial cells, which leads to cell death [ 20 , 21 ]. Brigotti et al reported detecting Stx2 in polymorphonuclear leukocytes circulating in the blood of children with HUS [ 22 ].…”
Section: Resultsmentioning
confidence: 53%
“…The bacterial virulence factors can direct their way to the target organs by gaining access to the bloodstream, causing widespread target organ damage, such as renal failure or brain damage (Villysson et al 2017). One of the main mechanisms of toxin-induced systemic and targeted organ injury involves the transport of bacterial toxin through microvesicles (MV).…”
Section: Lipid Microvesicle-mediated Trafficking Of Toxinsmentioning
confidence: 99%
“…In acute cases of STEC-HUS infections, the MVs, mostly from platelets and monocytes bearing tissue factor, binds to annexin V through PS. The presence of tissue factor and PS on MVs contribute to the formation of microthrombi during the acute phases of infection (Villysson et al 2017).…”
Section: Lipid Microvesicle-mediated Trafficking Of Toxinsmentioning
confidence: 99%